2017
DOI: 10.1063/1.4999408
|View full text |Cite
|
Sign up to set email alerts
|

Fokker-Planck equation for the non-Markovian Brownian motion in the presence of a magnetic field

Abstract: In the present study, we have proposed the Fokker-Planck equation in a simple way for a Langevin equation of motion having ordinary derivative (OD), the Gaussian random force and a generalized frictional memory kernel. The equation may be associated with or without conservative force field from harmonic potential. We extend this method for a charged Brownian particle in the presence of a magnetic field. Thus, the present method is applicable for a Langevin equation of motion with OD, the Gaussian colored therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 96 publications
1
36
0
Order By: Relevance
“…Very recently the Fokker-Planck equation has been proposed in the natural phase space in a simple way for arbitrary frictional memory kernel [53] and additive thermal noise. The Fokker-Planck equation in the phase space also has been derived in a recent Ref.…”
Section: The Modelmentioning
confidence: 99%
“…Very recently the Fokker-Planck equation has been proposed in the natural phase space in a simple way for arbitrary frictional memory kernel [53] and additive thermal noise. The Fokker-Planck equation in the phase space also has been derived in a recent Ref.…”
Section: The Modelmentioning
confidence: 99%
“…Here it has been shown that a few extra terms appear in the FPE compared to Ref. [1]. Then to reexamine our calculation we started with the relevant Langevin equations of motion [1,2],…”
mentioning
confidence: 93%
“…In a recent paper [1], we derived the Fokker-Planck equations using an alternative method for the non-Markovian dynamics for a free particle and the harmonic oscillator, respectively. Then we extend this method for the non-Markovian dynamics in the presence of a magnetic field.…”
mentioning
confidence: 99%
See 2 more Smart Citations